THE SCHOOL EFFECTIVENESS RESEARCH PROGRAMME: TOWARDS A PRACTIONERS’ PERSPECTIVE IN THE LATIN AMERICAN CONTEXT - Sandoval-Hernández, Andrés; Barrón Pastor, Juan Carlos (Revista Enfoques Educacionales, 2017)
Based on the Lakatos’ notion of research programmes, this paper analyses the structure of the School Effectiveness Research Programme as it has been developed mainly in the UK and USA, and reviews the main criticisms that have recently risen, stressing those regarding its adherence to a positivist epistemology and the lack of context-sensitive models for school effectiveness. The paper concludes in outlining some possible basis for a new research programme which would suit better the Latin American social reality. This programme would include shifting towards a more critical epistemology and the use of a methodology and theoretical-conceptual tools that would allow the design of context-sensitive (both, micro and macro contexts) models for school effectiveness promoting a gradual inclusion of practitioners’ perspectives.